Training needs and its determinants of KVK-Subject Matter Specialists in West Bengal and Bihar - Deboshmita Dey; Ananthan P.S; Shivaji Argade; Munilkumar Sukham; Mukesh Kumar (Journal of Indian Fisheries Association, 2023)
Subject Matter Specialists (SMS) in Krish Vigyan Kendras (KVK) are the district level extension functionaries, primarily refining and demonstrating location-specific technologies, and training and communicating with the farming community and grassroots extension workers. The changing agrarian scenario underscores the need for capacity development of KVK-SMS based on their identified training needs. This study assessed the training needs of 116 KVK-SMS in the states of West Bengal and Bihar, using a structured and pre-tested online survey tool in early 2022. Respondent SMS primarily consisted men (78%) who were largely young (42 %). Half of them (56%) were PhD holders while the rest had Masters with a specialisation in Fisheries (14%), Horticulture (14%), Agriculture Extension (13&), Agronomy (12%) and Animal Science (9%), and had an average service of 6-7 years. The study revealed perceived inadequacy in budget and infrastructure facilities for performing the mandated activities especially in recently established KVKs. Two-third of SMS (68%) were only partially satisfied with their present working conditions. Half of them used social media to regularly connect with farmers. Of 14 thematic areas, three most sought after training areas of SMS were entrepreneurship development (WSM score 49%), success story documentation (WSM score 46), and BMPs in aquaculture (WSM score 45%). Spearman’s rank correlation showed no relationship between SMS training needs and their profile characteristics like age, experience, specialisation, host institution, state, etc. Majority preferred short courses (5-7 days) conducted in physical mode. Respective ICAR ATARI may work with ICAR institutions, Agricultural Universities, and Extension Training Institutes to organise the demand-based capacity development programs for KVK-SMS in West Bengal and Bihar.